Korelasi Komunikasi Terapeutik Perawat terhadap Kepuasan Pasien Rawat Inap Kelas III - Putri Syalistia Wati; Akhmad Faozi; Dello Yuliana Rahmat (Journal of Health, 2025)
Communication used in services can result in patient satisfaction. The communication used is therapeutic communication carried out by nurses. Purpose of this study is to determine how nurses' therapeutic communication relates to the level of patient satisfaction. Type of research used is quantitative with a cross-sectional research design. determining the sample in the study using quota sampling, the research sample consisted of 60 patients. After testing the hypothesis with Spearman Rho, the results show that the significance value is 0.001 < (0.05) which means that the nurse's therapeutic communication is correlated or related to patient satisfaction, the direction of the correlation also shows a positive value, and the correlation coefficient value is 0.460 where this value indicates that the nurse's therapeutic communication and patient satisfaction have a fairly strong relationship. Nurse's therapeutic communication is considered to be very good, it is also known that some patients of class III inpatient rooms are very satisfied with the nurse's therapeutic communication, based on the results of the study it can be concluded that there is a relationship between the nurse's therapeutic communication and the satisfaction of class III inpatients where the value of the relationship is quite strong with the direction of the study showing a positive correlation.